Trucking country : the road to America's Wal-Mart economy - Hamilton, Shane, 1976- (Politics and society in twentieth-century America., 2008)
Trucking Country is a social history of long-haul trucking that explores the contentious politics of free-market capitalism in post-World War II America. Shane Hamilton paints an eye-opening portrait of the rural highways of the American heartland, and in doing so explains why working-class populist voters are drawn to conservative politicians who seemingly don't represent their financial interests. Hamilton challenges the popular notion of "red state" conservatism as a devil's bargain between culturally conservative rural workers and economically conservative demagogues in the Republican Part